2020
DOI: 10.1111/cod.13509
|View full text |Cite
|
Sign up to set email alerts
|

Photodermatitis from topical phenothiazines: A case series

Abstract: In Europe, contact photosensitivity to phenothiazines is known particularly in southern countries. Topical phenothiazines are widely used and sold over-the-counter for the treatment of mosquito bites and pruritus in France. Objective:To report a series of cases with photodermatitis to topical phenothiazines. Method:A retrospective study of cases of contact dermatitis to phenothiazines seen in French photodermatology centres was performed. Results:In all, 14 patients with the diagnosis of contact dermatitis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…14,15 A recent study reported a series of cases of PACD caused by topical phenothiazines, widely used as over-thecounter (OTC) antipruritic drugs in France. 16 Chlorpromazine, which is a phenothiazine, led to PACD in the greatest number of patients, with 23.8% of the patients recruited reporting positive PACD reactions, but only 13.0% of those reactions were of current or past relevance. Analysis of clinical relevance (13%) showed that only seven patients were health-care workers or pharmaceutical workers who handled phenothiazines for occupational needs, while most of the patients used drugs containing phenothiazines (especially promethazine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 A recent study reported a series of cases of PACD caused by topical phenothiazines, widely used as over-thecounter (OTC) antipruritic drugs in France. 16 Chlorpromazine, which is a phenothiazine, led to PACD in the greatest number of patients, with 23.8% of the patients recruited reporting positive PACD reactions, but only 13.0% of those reactions were of current or past relevance. Analysis of clinical relevance (13%) showed that only seven patients were health-care workers or pharmaceutical workers who handled phenothiazines for occupational needs, while most of the patients used drugs containing phenothiazines (especially promethazine).…”
Section: Discussionmentioning
confidence: 99%
“…Phenothiazines are known as a class of organic compounds that are considered to be representative drugs for inducing phototoxic reactions as well as PACD 14,15 . A recent study reported a series of cases of PACD caused by topical phenothiazines, widely used as over‐the‐counter (OTC) antipruritic drugs in France 16 . Chlorpromazine, which is a phenothiazine, led to PACD in the greatest number of patients, with 23.8% of the patients recruited reporting positive PACD reactions, but only 13.0% of those reactions were of current or past relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Topical phenothiazine antihistamine preparations are well-known strong contact and photocontact sensitizers and therefore they have been withdrawn in many countries. 1,5 Our patient developed dermatitis after a 6-month administration of promazine oral drops. Because of the patient's difficulties in swallowing, the oral drug spilled onto the skin surrounding her mouth and possibly acted as a photocontact allergen.…”
Section: Discussionmentioning
confidence: 79%
“…These old heterocyclic drugs are well‐known phototoxic compounds, but they can also induce allergic and photoallergic dermatitis. Topical phenothiazine antihistamine preparations are well‐known strong contact and photocontact sensitizers and therefore they have been withdrawn in many countries 1,5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation